2019
DOI: 10.1371/journal.pone.0217542
|View full text |Cite|
|
Sign up to set email alerts
|

A transcriptional signature associated with non-Hodgkin lymphoma in the blood of patients with Q fever

Abstract: Coxiella burnetii , the agent causing Q fever, has been associated with B-cell non-Hodgkin lymphoma (NHL). To better clarify this link, we analysed the genetic transcriptomic profile of peripheral blood leukocytes from patients with C . burnetii infection to identify possible links to lymphoma. Microarray analyses revealed that 1189 genes were expressed differently (p <.001 and fold change ≥4) in whole blood of patients with C . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Over the past 3 years, we have reported results suggesting that the bacterium Coxiella burnetii , responsible of Q fever, was associated with a higher frequency of Non-Hodgkin Lymphoma (NHL) in C. burnetii -infected patients compared to the general population (Melenotte et al, 2016). Recently, we investigated the transcriptional signature that could be associated with the development of NHL in Q fever patients and found an over-expression of genes involved in anti-apoptotic process and a repression of pro-apoptotic genes (Melenotte et al, 2019). Since cell surface expression of E-cad and release of sE-cad have been associated to various pathogenic bacteria known for inducing solid tumors, we have also investigated the levels of expression of these molecules in Q fever patients and observed a significant release of sE-cad in their sera and a down-regulation of E-cad mRNA expression.…”
Section: Release Of Soluble E-cadherin After Bacterial Infection As Amentioning
confidence: 99%
“…Over the past 3 years, we have reported results suggesting that the bacterium Coxiella burnetii , responsible of Q fever, was associated with a higher frequency of Non-Hodgkin Lymphoma (NHL) in C. burnetii -infected patients compared to the general population (Melenotte et al, 2016). Recently, we investigated the transcriptional signature that could be associated with the development of NHL in Q fever patients and found an over-expression of genes involved in anti-apoptotic process and a repression of pro-apoptotic genes (Melenotte et al, 2019). Since cell surface expression of E-cad and release of sE-cad have been associated to various pathogenic bacteria known for inducing solid tumors, we have also investigated the levels of expression of these molecules in Q fever patients and observed a significant release of sE-cad in their sera and a down-regulation of E-cad mRNA expression.…”
Section: Release Of Soluble E-cadherin After Bacterial Infection As Amentioning
confidence: 99%
“…The Rituximab used in the treatment of NHL patients may overcome BCL-2-mediated chemoresistance through the inhibition of IL-10, thus down-regulating BCL-2 expression (Park et al, 2009). By investigating a specific gene signature for Q fever patients by microarray, we recently found that specific genes involved in anti-apoptotic process were over-expressed compared to samples from healthy donors, and that pro-apoptotic genes were repressed (Melenotte et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, we investigated the transcriptional signature associated with the development of NHL using the PBMCs of patients with Q fever. By analyzing their gene expression by microarray, we found the over-expression of genes involved in anti-apoptotic process and repression of pro-apoptotic genes as compared to samples from healthy donors (Melenotte et al, 2019). Yet, the early molecular events controlling the balance between remission and progression toward more severe diseases remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted by Melanotte et al, it was demonstrated that patients with C . burnetii lymphadenitis presented significantly elevated levels of BCL2 and ETS1 mRNAs, which may indicate the upregulation of anti-apoptotic processes and the fact that lymphadenitis might constitute a critical step towards lymphomagenesis [ 121 ]. The association of Q fever with NHL requires further study.…”
Section: Coxiella Burnetii ( C Burnetii ) and Various Nhlmentioning
confidence: 99%